The Swedish furniture industry – a study of strategic groups and performance. Issue 6 (2nd November 2022) - Brege, Staffan; Nord, Tomas; Brege, Harald; Holtström, Johan; Sjöström, Roland
ABSTRACT: The scope of this article is a longitudinal strategic group study with a special focus on the strategic group-performance relationship. The empirical context is the Swedish Furniture Industry, a very heterogeneous industry well suited for this type of "middle-ground study" between industry and firm levels. The research questions are finding suitable strategic dimensions to use when in a next step splitting up into different strategic groups followed by an analysis of the strategic group-performance relationship. Finally, an explanatory approach is taken with the purpose of increasing our understanding of performance differences between strategic groups. The empirical investigation is a total population study of 143 companies (micro companies excluded) and the period of analysis is 2004 up to 2017. Empirical data consist of yearly income statements, public statistics, results from two questionnaires and multiple (firm) case descriptions. The explanatory part is of a qualitative nature and points out the major differences between the strategic groups regarding environmental forces and competitive advantage. Nine strategic groups are identified and stable performance differences between groups are noted which are mainly related to different demand conditions between three customer sectors – household, institutional and B2B – but also to the mix of micro product/customer segments within these sectors.